The Effectiveness of A Teaching Program Based on Some of Principles of TRIZ Theory for Teaching Science in The Development of Reflective Thinking Skills at The 2nd Intermediate Grade Students - Alzaidi, Waleed Saleh; Almutawa, Naif Abdulaziz (Journal of Curriculum and Teaching Methodology, 2023)
This research sought to reveal the effectiveness of a teaching program based on some principles of TRIZ theory for teaching science in developing reflective thinking skills of second-grade students. To achieve this goal, the research used the quasi-experimental methodology; where the sample consisted of (64) students from Ibn Al-Qayyim intermediate school in Dawadmi in Riyadh region, Kingdom of Saudi Arabia. They were divided randomly in two equal groups: an experimental group and a control group. The researcher used the reflective thinking skills test, and found statistically significant differences at the level of (α ≤0.05) between the mean scores of the experimental and control groups in the post test of reflective thinking skills for the experimental group. In light of this, the researcher introduced some of recommendations: training science teachers on using the principles of TRIZ theory at all educational levels, and benefiting from the teacher’s guide in designing other programs.